Status of information, education, and communication as perceived by clients receiving antenatal care at Chiradzulu District Hospital in Malawi - Gaily Graysham Lungu; Elizabeth Chodzaza; Martha Kamanga; Wanangwa Chikazinga; Diana Jere (BMC, 2023)
Abstract Background Information, education, and communication is a strategy to spread awareness through communication channels to a target audience to achieve a desired positive result. Women are supposed to receive information, education, and communication at each contact with the health worker during antenatal care. In Malawi, information, education, and communication for antenatal care is inadequate despite high antenatal care coverage. Most women do not receive it as stipulated. This could be one of the reasons that maternal and neonatal mortality is high. The provision of information, education, and communication is supposed to help in reducing maternal mortality because it is intended to develop positive attitudes towards health behaviours to support pregnant women accessing health services when required. This study, therefore, assessed the status of information, education, and communication as perceived by clients receiving antenatal care at Chiradzulu District Hospital in Malawi. Methods A descriptive study design with a sample of 384 pregnant women attending antenatal care was used. The sample size for the study was calculated using Lemeshow, Hosmer, Klar and Rwanga's formula. Systematic random sampling method was used to select the study participants. Data were analysed using a statistical package for social sciences software version 20.0. Results Findings revealed that information, education, and communication provided during antenatal care were inadequate. Most information was offered. However, no topic was rated adequate by 80% of the respondents according to the Likert Scale that was used. The majority of the respondents (71.4%, n = 274) (95% CI 66.5. 75.8) preferred to receive information, education, and communication from midwives who are in the category of skilled attendants. Results further showed that more than half of the respondents participated passively and spent little time receiving information, education, and communication. Conclusion The findings signify that information, education, and communication provided to women receiving antenatal care at Chiradzulu District Hospital had some gaps. It was inadequate and some topics were not taught. The target audience participated passively. It is recommended that midwives should provide the information, education, and communication and must have adequate contact time with the women. This is so because they are believed to be trusted sources of information.